(untitled) (Práxis Educativa, 2023)
This is an account of the author’s participation in the Working Group of the National Commission for Research Ethics (CONEP), from 2017 to 2021, in charge of preparing the Resolution on the classification of research and the processing of research protocols in the CEP/CONEP System (CNS Resolution no. 674/2022). The article was divided onto four parts: preview, protection, participation and pendency. An anthropological perspective on state institutions supports the reflection on the application of the notion of vulnerability in the ethical evaluation of research. Keywords: Ethics in research. CNS Resolution no. 674/2022. Protection.